Secretion of Hepatitis C Virus replication intermediates reduces activation of toll-like receptor 3 in hepatocytes - Grünvogel, Oliver; Colasanti, Ombretta; Lee, Ji Young; Klöss, Volker; Esser-Nobis, Katharina; Mutz, Pascal; Hoffmann, Katrin; Mehrabi, Arianeb; Koschny, Ronald; Gotthardt, Daniel; Schnitzler, Paul; Binder, Marco; et al. (Gastroenterology, 2018)
Background & Aims - Hepatitis C virus (HCV) infections most often result in chronic outcomes, although the virus constantly produces replication intermediates, in particular double-stranded RNA (dsRNA), representing potent inducers of innate immunity. We aimed to characterize the fate of HCV dsRNA in hepatocyte cultures to identify mechanisms contributing to viral persistence in presence of an active innate immune response. - Methods - We analyzed hepatocyte-based culture models for HCV for induction of innate immunity, secretion of virus positive- or negative-strand RNA, and viral replication using different quantification methods and microscopy techniques. Expression of pattern recognition receptors was reconstituted in hepatoma cells by lentiviral transduction. - Results - HCV-infected cells secrete substantial amounts of virus positive- and negative-strand RNAs in extracellular vesicles (EVs), toward the apical and basolateral domain of hepatocytes. Secretion of negative-strand RNA was independent from virus production, and viral RNA secreted in EVs contained higher relative amounts of negative-strands, indicating that mostly virus dsRNA is released. A substantial part of viral replication complexes and dsRNA was found in the endosomal compartment and multivesicular bodies, indicating that secretion of HCV replication intermediates is mediated by the exosomal pathway. Block of vesicle release in HCV-positive cells increased intracellular dsRNA levels and increased activation of toll-like receptor 3, inhibiting HCV replication. - Conclusions - Using hepatocyte-based culture models for HCV, we found a portion of HCV dsRNA intermediates to be released from infected cells in EVs, which reduces activation of toll-like receptor 3. This represents a novel mechanism how HCV evades host immune responses, potentially contributing to viral persistence.
Gesehen am 22.05.2019